STANDAR PENGISIAN JABATAN PIMPINAN SKPD BIROKRASI DI KABUPATEN PURBALINGGA - Sulistyowati, Sulistyowati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This research conducted to understand how the standard of filling the leader of government agency at regional level (SKPD) position in order to increase capability and profesionality of bureaucracy in Purbalingga region has been following the Merit System or not , in order to realize Good Government and also Clean Government as has been expected. Moreover, to understand there is political penetration or not in order to fill the leader of government agency at regional level (SKPD) position in Purbalingga regency, during the Regent (Bupati) Heru Sudjatmiko leadership period in more than 3 (three) years.The result of the study showed that the standard of filling the leader of government agency at regional level (SKPD) position in Purbalingga regency had been done accord to procedure which is through *BAPEJAKAT Team and through Fit and proper-test process, however, the final decision still on Regency Leader’s hand in this term is the Regent (Bupati). It can be prove by the frequent investiture on Structural position of Eselon II , especially for the leader of government agency at regional level (SKPD) position in Purbalingga regency. The Performance System has not yet applied as one of the standard of filling officer position in regional level, and also the morality factor should be the main emphasis as well.